ANALISIS PENINGKATAN KUALITAS PRODUK KITCHEN SET DAN JENDELA MENGGUNAKAN METODE LEAN MANUFACTURING - Putra, Ade Sulistiya (JUSTI (Jurnal Sistem dan Teknik Industri), 2023)
ABSTRACT The kitchen set and windows are products from UD MOELJAY. The kitchen set is a product that uses aluminum and glass. During the production process, the kitchen set had 2 defects, namely the glass broke when cutting and the product could not be installed. Windows are also one of the products from UD MOELJAY which uses wood and glass materials. The window has 2 defects, namely the glass broke when cutting and the product could not be installed. The existence of these defects indicates that there is waste in the production process. Therefore, this research was conducted to solve problems using the Lean Manufacturing method. Value Stream Mapping (VSM) is used to describe the flow of the production process and information that occurs in the production process. Based on the results of the VSM analysis and proposed corrective actions, it is known that there has been an increase in time efficiency in the process of working on kitchen sets and windows. In the kitchen set work process, the Cycle Time efficiency was 53.56% or 142.65 minutes and the lead time efficiency was 62.88% or 152.85 minutes. Meanwhile, in the window work process, the Cycle Time efficiency was 66.40% or 103.31 minutes and the lead time efficiency was 75.61% or 103.32 minutes.